Use of Polyguanidine-Derivatives-Based Biocides for Microbial Growth Inhibition and for the Development of a Novel Polyethylene-Based Composite Material Resistant to the Formation of Multispecies Microbial Biofilms - Zhurina, Marina; Gannesen, Andrei; Martyanov, Sergey; Kallistova, Anna; Gerasin, Victor; Sivov, Nikolai; Tikhomirov, Vsevolod; Myint, Ahkar Kaung; Plakunov, Vladimir (KnE Life Sciences, 2022)
This study aimed to investigate the dependence of the biocidal activity of polyguanidine (co)polymers on their structure during the formation of biofilms by active PE-degrading cultures of model microorganisms. The Bc-2 copolymer of methacryloyl guanidine hydrochloride (MGHC) and diallyldimethylammonium chloride (DADMAC), which suppressed both the formation of biofilms and the growth of planktonic cultures, exhibited the highest activity. When PE was exposed in tropical soil, the composition of the microbial community on the PE surface differed significantly from that of the community in the surrounding soil. In particular, the proportion of Actinobacteria increased from 7% to 29%, while the proportion of Bacteroidetes decreased from 38% to 8%. Keywords: biofilms, polyhexamethylene guanidine salts, dynamics of biofilm formation, antibiofilm effect, composite materials